INTERPRETATION OF HIDDEN PRAGMALINGUISTICS IN ZULFIYA KUROLBOY KIZI'S WORKS (Examples of stories: "Jealousy", "Eve", "Bride") (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
This article analyzes pragma linguistics and its important aspects, such as hidden pragma linguistics, presupposition, and hidden meaning, based on the stories of Zulfiya Kurolboy's daughter.